Macroeconomics from the bottom-up - Delli Gatti, Domenico; Desiderio, Saul; Gaffeo, Edoardo; Cirillo, Pasquale; Gallegati, Mauro (New Economic Windows,2039-411X, 2011)
The recent economic events driven by the big financial crisis of 2007-08 has cogently put to the fore the limits and drawbacks of the ruling research paradigm in macroeconomics. This volume goes to the root of the problem by offering a workable alternative to the renowned issue of the microeconomic foundations of macroeconomic theory. Bringing together techniques from agent-based computational economics and statistical validation, the authors set the stage for a paradigmatic shift, elaborate on it with practical examples and provide an agenda for future research.